DETERMINING COMPRESSION AND FUEL RATIOS FOR A MODIFIED 4-STROKE ENGINE - Hedyan Restu Pratama (TRAKSI, 2022)
Motorcycles are one of the simple motorized vehicle transportation tools that are widely used by people today. The formulation of the problem in this research is what is the result of the compression ratio value that is obtained after the research and what is the compression value according to the machine. The purpose of this study was to determine the value of the compression ratio on a modified engine and to determine the fuel used in the compression ratio. The method used in this study is a literature study, calculating and determining the amount of compression. The results obtained from the calculation to get the compression ratio from 8.7 : 1 to 10.7 : 1 then the cutting height of the cylinder is 1.33mm, and To get the compression ratio from 10.7 : 1 to 11.3 : 1, then the cutting height cylinder is 0.31 mm. From the calculation of the Compression Ratio 1, 2, and 3, to achieve the final Compression Ratio value of 11.3: 1, a total block cutting of 1.64 mm is needed. And based on table B data, it can be seen that the compression ratio value of 11-12: 1 is using Pertamax Turbo or you can also use Shell V-Power and Performance 95. Therefore, it can be concluded that a 4-stroke motorcycle engine with a compression ratio of 11.3: 1 can use fuel with an octane rating of 95 with the type of fuel Pertamax Turbo, Shell V-Power, or Performace 95. With this compression ratio value, if you look at the ideal fuel table according to the compression ratio value, the octane value of the fuel increases to 95, and the fuel used is Pertamax Turbo, Shell V- Power, or Performance 95. The compression ratio value of 11.3 : 1 will be more in accordance with the specifications of the engine and also the needs of the user because the compression ratio value is not too high and not too low. Therefore this modified 4-stroke engine can be used for daily and long-distance purposes.